THE ROLE OF MYTH IN SUSTAINAINING BASANG TAMIANG POTTERY IN KAPAL VILLAGE BADUNG REGENCY - Mudra, I Wayan; Muliawati, Ni Putu (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
Pottery craft products produced by craftsmen in Banjar Bangsatamiang, Kapal Village, Mengwi District, Badung Regency, their existence is still continuing until now, it is believed that there are myths that play a role in them. This study aims to discuss the role of myths in the sustainability of pottery craft products by craftsmen in Banjar Basangtamiang. Data were collected using observation, interview, and documentation techniques, determination of data sources with purposive sampling and data analysis with Roland Barthes' myth theory. The results of the study show that the beliefs of Banjar Basang Tamiang craftsmen discussed from Roland Barthes' semiotic theory can be called myths in the first level of denotative sign reading and connotative sign reading at the second level. These myths ideologically bind craftsmen to continue to pursue pottery crafts as a profession for a living. These myths play a positive role in the sustainability of Basang Tamiang pottery crafts in the future so that they can exist until now .